2013
DOI: 10.1016/j.jcp.2012.12.014
|View full text |Cite
|
Sign up to set email alerts
|

Coarse-grained simulation of transmembrane peptides in the gel phase

Abstract: We use Dissipative Particle Dynamics simulations, combined with parallel tempering and umbrella sampling, to investigate the potential of mean force between model transmembrane peptides in the various phases of a lipid bilayer, including the low-temperature gel phase. The observed oscillations in the effective interaction between peptides are consistent with the different structures of the surrounding lipid phases.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 34 publications
0
1
0
Order By: Relevance
“… 37 It calculates the dynamic behavior of the system based on molecular dynamics. Compared to molecular dynamics simulations, DPD can take longer time steps and is more suitable for simulating solution systems with complex components, such as polymer, 40 surfactant, 41 gels, 42 and microemulsions. 39 In a study conducted by Li 43 et al, the interfacial behavior of sodium dodecylbenzenesulfonate [surfactant sodium dodecyl benzenesulfonate (SDBS)] and sodium oleate (OAS) surfactants in oil–water emulsification was investigated using DPD and the study revealed that the stacking behavior on the interfacial film is influenced by the surfactant concentration and the structure of the hydrophobic tail in the oil phase.…”
Section: Introductionmentioning
confidence: 99%
“… 37 It calculates the dynamic behavior of the system based on molecular dynamics. Compared to molecular dynamics simulations, DPD can take longer time steps and is more suitable for simulating solution systems with complex components, such as polymer, 40 surfactant, 41 gels, 42 and microemulsions. 39 In a study conducted by Li 43 et al, the interfacial behavior of sodium dodecylbenzenesulfonate [surfactant sodium dodecyl benzenesulfonate (SDBS)] and sodium oleate (OAS) surfactants in oil–water emulsification was investigated using DPD and the study revealed that the stacking behavior on the interfacial film is influenced by the surfactant concentration and the structure of the hydrophobic tail in the oil phase.…”
Section: Introductionmentioning
confidence: 99%